CRITICAL REASONING ISLAMIC RELIGIOUS EDUCATION AND THE CHALLENGES OF NATIONAL DEMOCRACY IN PLURALIST COUNTRIES - Nanang Faisol Hadi (International Journal Labs, 2022)
This article analyzes how Islamic education and the challenges of national democracy in the midst of a pluralist state in the United States. A country that is very complex in various needs of human life, including in the field of religious privacy. More specifically about Islamic education, its implications and implementation. Application of Islamic education curriculum and practice of religious education in schools. It is even more challenging when it is collided with the conditions of a democratic, multicultural and multi-religious country. So the concept of national democracy needs to have a place in the discussion. Because it will definitely involve a conflict between progressive liberal Islam and conservative salafi Islam. The purpose of this paper is oriented towards efforts to appreciate and contextualize the claims of the Islamic religion in accordance with the ideals of reflective education, rational thinking, mutual respect, and equality in citizenship. The method used in this research is qualitative with library research. Applying a liberal and progressive Islamic perspective in education encourages Muslim students to develop the capacity for critical thinking, moral reasoning, and democratic deliberation. They learn to recognize the politics of religious interpretation, to contextualize and historicalize Islamic knowledge, and how it might be influenced by social, historical, and political forces. One more limitation in implementing Islamic education in the United States relates to the quality of teachers. Half of Islamic studies teachers are not certified or licensed required for education. Liberal and advanced Islamic education encourages Muslim students to build a critical spirit and a confident attitude about Islamic teachings so that they communicate their religion in a convincing and deliberative way.